2015
DOI: 10.1177/1049732315577607
|View full text |Cite
|
Sign up to set email alerts
|

Health as Submission and Social Responsibilities

Abstract: By examining women's experiences with type II diabetes, we explore how illness can provide resources to construct meanings of everyday life in Javanese culture. We conducted in-depth interviews with 30 female participants in Central Java, Indonesia, and adopted grounded theory for data analysis. We identified four themes that diabetes serves as resources for women in Indonesia to (a) normalize suffering, (b) resist social control, (c) accept fate, and (d) validate faith. We concluded by noting three unique asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Indonesian people consider themselves healthy if they can perform their everyday activities without disruption. Thus, people generally sought help when symptoms hindered these [21,22,25,28,37,39,42,45,51,56,66,67,71,77]. For example, Eeuwijk [71] described that most older people sought care from health professionals for rheumatism because it hindered their activities.…”
Section: Lay Concepts Of Health and Illnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Indonesian people consider themselves healthy if they can perform their everyday activities without disruption. Thus, people generally sought help when symptoms hindered these [21,22,25,28,37,39,42,45,51,56,66,67,71,77]. For example, Eeuwijk [71] described that most older people sought care from health professionals for rheumatism because it hindered their activities.…”
Section: Lay Concepts Of Health and Illnessmentioning
confidence: 99%
“…Health is a physical status that cannot be achieved without individuals' spiritual wellbeing. Life in general should be balanced physically and spiritually, between individual and social life, so that a status of "harmony" can be reached [42,57]. The Indonesian government recognizes six official religions: Islam, Catholicism, Protestantism, Hinduism, Buddhism, and Confucianism [105].…”
Section: Lay Concepts Of Health and Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The flowchart of the study selection process is demonstrated in Figure 1 (Figure according to Prisma statement). More than half of the studies (13 studies) included were qualitative (Samuel-Hodge et al, 2000; Daaleman, Kuckelman Cobb, & Frey, 2001;Iwasaki et al, 2005;Devlin et al, 2006;Polzer & Miles, 2007;Cattich & Knudson-Martin, 2009;Casarez et al, 2010;Unantenne, Warren, Canaway, & Manderson, 2013;Gupta & Anandarajah, 2014;Pitaloka & Hsieh, 2015;Rivera-Hernandez, 2015;Namageyo-Funa, Muilenburg, & Wilson, 2015; Spruill, Magwood, Nemeth, & P. Darvyri et al…”
mentioning
confidence: 99%